A gamified app on emotion recognition and anger management for pre-school children - Nicolaidou, Iolie; Tozzi, Federica; Antoniades, Athos (My University, 2022)
Anger is a common reason for child mental-health referrals. Therefore, children need to develop emotion recognition and anger management skills from an early age. Gamified apps can deliver mental health interventions for children, but this research area is still in its infancy. A gamified, interactive storytelling mobile app, which was designed as a stress prevention intervention for young children was tested by 20 preprimary school children (4–6 years old) during a science festival. The study aimed to examine children's understanding of three anger management techniques demonstrated through the app. The main data source of the study consisted of 20 individual audiotaped semi-structured children interviews. Interviews were transcribed verbatim and analyzed using a qualitative data analysis software. Findings showed that the story is comprehensible by preschool children. Eleven out of 20 children could recall at least one anger management technique but only seven (7/20) could identify or demonstrate a technique that can be applied in a stressful situation in real life. There is a need to embed additional scaffolding, prompts, or motivational rewards for children to engage with more than one anger management technique and to avoid misconceptions. Gamified apps can potentially be effective behavioral intervention technologies to deliver emotional education to young children affordably, accessibly, and engagingly.
Keywords: Emotion education; Behavioral intervention technologies; Preschool education; Stress prevention intervention; Anger management; Gamified apps